The Effect of Additives on the Early Stages of Growth of Calcite Single Crystals. Issue 39 (18th August 2017) - Kim, Yi‐Yeoun; Freeman, Colin L.; Gong, Xiuqing; Levenstein, Mark A.; Wang, Yunwei; Kulak, Alexander; Anduix‐Canto, Clara; Lee, Phillip A.; Li, Shunbo; Chen, Li; Christenson, Hugo K.; Meldrum, Fiona C.
Abstract: As crystallization processes are often rapid, it can be difficult to monitor their growth mechanisms. In this study, we made use of the fact that crystallization proceeds more slowly in small volumes than in bulk solution to investigate the effects of the soluble additives Mg 2+ and poly(styrene sulfonate) (PSS) on the early stages of growth of calcite crystals. Using a "Crystal Hotel" microfluidic device to provide well‐defined, nanoliter volumes, we observed that calcite crystals form via an amorphous precursor phase. Surprisingly, the first calcite crystals formed are perfect rhombohedra, and the soluble additives have no influence on the morphology until the crystals reach sizes of 0.1–0.5 μm for Mg 2+ and 1–2 μm for PSS. The crystals then continue to grow to develop morphologies characteristic of these additives. These results can be rationalized by considering additive binding to kink sites, which is consistent with crystal growth by a classical mechanism. Abstract : Rooms for crystals : By precipitating calcite crystals within confined volumes, where growth proceeds more slowly, in a "Crystal Hotel", it is shown that additives only affect the shape of the crystals once they have reached sizes of at least 100 nm. As a crystal grows, the density of specific surface (kink) sites to which the additives bind increases. Changes in the crystal shape will only become evident when this density is high enough.